Answer:
(x-1) (x+4)
Step-by-step explanation:
i used something called the box method, basically the way i got the answer is what equals 3 when added, but multiplies to make -4
Answer:
First account (simple interest)
Step-by-step explanation:
The amount of interest earned by the first account is ...
I = Prt = $2000·0.04·7 = $2000·0.28 = $560
The amount in the second account at the end of 7 year is ...
FV = P·(1+r)^t = $2000·1.02^7 = $2297.37
so you have earned $297.37 in interest on the second account.
$560 is more than $297, so the First Account (simple interest) earns more money.
Here are the basic steps to follow to simplify an algebraic expression:<span>remove parentheses by multiplying factors.
use exponent rules to remove parentheses in terms with exponents.
combine like terms by adding coefficients.
<span>combine the constants.</span></span>
Answer:
x = 4
y = 3
Step-by-step explanation:
<u>Given </u><u>equations </u><u>:</u><u>-</u>
<u>Second</u><u> </u><u>equation</u><u> </u><u>can </u><u>be</u><u> written</u><u> as</u><u> </u><u>,</u><u> </u>
<u>Adding</u><u> </u><u>them </u><u>:</u><u>-</u><u> </u>
- -3y + 2y = 2 -5
- -y = -3
- y = 3
<u>Put </u><u>this </u><u>in </u><u>(</u><u>ii)</u><u> </u><u>:</u><u>-</u><u> </u>
- x = 3y - 5
- x = 3*3 - 5
- x = 9 -5
- X = 4